Pengaruh Teknologi Informasi Dan Komunikasi (TIK) Dalam Administrasi Publik - Indriati Amirullah (Institut Nalanda, 2023)
This research focuses on the influence of information and communication technology (ICT) in public administration. Technology has changed the way many sectors work, including public administration, and this research aims to understand how these changes have affected the efficiency and effectiveness of public services. Using a variety of research methods, we examine how ICT has influenced administrative processes, as well as the resulting impacts, both positive and negative. Initial findings suggest that the use of ICT in public administration can bring significant improvements in the efficiency and effectiveness of services, although there are also challenges to be overcome. This research is expected to provide new insights into how best to utilize ICT in public administration for optimal results.